2016
DOI: 10.1371/journal.pone.0157805
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Factors that Shape Gender Attitudes in Early Adolescence Globally: A Mixed-Methods Systematic Review

Abstract: BackgroundEarly adolescence (ages 10–14) is a period of increased expectations for boys and girls to adhere to socially constructed and often stereotypical norms that perpetuate gender inequalities. The endorsement of such gender norms is closely linked to poor adolescent sexual and reproductive and other health-related outcomes yet little is known about the factors that influence young adolescents’ personal gender attitudes.ObjectivesTo explore factors that shape gender attitudes in early adolescence across d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
323
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 378 publications
(348 citation statements)
references
References 109 publications
(337 reference statements)
16
323
2
7
Order By: Relevance
“…Research on social norms and gender attitudes shows that these are generally influenced by both peers and family behavior [3]. Our analysis supports that peer violence is associated with patriarchal gender attitudes.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Research on social norms and gender attitudes shows that these are generally influenced by both peers and family behavior [3]. Our analysis supports that peer violence is associated with patriarchal gender attitudes.…”
Section: Resultssupporting
confidence: 78%
“…A recent review found that male peer groups enforce competition, toughness, and heterosexual prowess. Boys who fail to achieve local masculinity standards are bullied and ridiculed by their peers [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender norms and gender attitudes are thought to play an important role in determining health outcomes, as patterns of sex-differential morbidity and mortality emerge in early adolescence [7,8]. Parents and peers are central to the development of adolescents' gender attitudes worldwide [9]. Peer relationships are especially salient as adolescents age [10].…”
mentioning
confidence: 99%